ANALISIS PENGARUH KEPERCAYAAN TERHADAP KEPUTUSAN PELANGGAN MENGGUNAKAN PRODUK IM3 DIKALANGAN MASYARAKAT KOTA LHOKSEUMAWE - Teuku Edyansyah (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
The purpose of this study was to determine the effect of trust in the customer’s decision to use the product IM3 in Lhokseumawe City. The population in this study is that people who use the product IM3 in Lhokseumawe City as a cellular telecommunications network. Because the population is not so clear in use IM3 products, the researchers took a sample of 100 respondents. The data obtained will be calculated and analyzed according to the model that are related. To see the effect, the authors use a simple linear regression model to see how much influence the customer’s trust in the costumer decision. Used in this study also tested the validity and reliability testing as well as the classical assumption of normality test and test heteroscedasticity. From the research, to find how many the role of trust (X) in influencing customer decisions (Y), can be seen in the R2 value of 0.408 or 40.8 % and the remaining 59.2 % is influenced by other variables not examined in this study (error term). T test or ttest for independent variable (X) obtained tcount 8.222, so the value of tcount 8.222 ttabel 1.984, where that trust in costumer (X) significantly influence customer decision variable (Y) with a significant level of 0.000. So it can be concluded that in this study received a hypothesis (H1) proposed that independent variables significantly influence customer decisions. Advice from the results of this study are encouraging consumer confidence in the IM3 level of sales that the company should continue to give satisfaction on an ongoing basis so that the percentage of sales in its services continues to increase.